Dampak Tenaga Kerja, IPTIK, dan ZIS Terhadap PDRB di Indonesia dengan I-HDI Sebagai Variabel Intervening - Muhammad, Nurcholis; Mustakim Muchlis; Nasrullah Bin Sapa; Kamaruddin, Kamaruddin (Al-Buhuts, 2024)
This study aims to determine the direct impact of labor, ICT-Development Index, and Zakat, Infaq, Shadaqa on Islamic Human Development Index and Gross Regional Domestic Product and the indirect impact of labor, ICT-Development Index, and Zakat, Infaq, Shadaqa variables on Gross Regional Domestic Product mediated by Islamic Human Development Index. This type of research is quantitative research using secondary data in the form of panel data from 27 provinces in Indonesia in 2018-2022. Data sources are obtained from BPS and BAZNAS. The data analysis model used is panel data analysis with the Random Effect Model (REM) approach and path analysis. The results of this study indicate that directly ICT-Development Index has a positive and significant impact on Islamic Human Development Index while labor and Zakat, Infaq, Shadaqa have a positive but insignificant impact on Islamic Human Development Index. Directly labor and ICT-Development Index have a positive and significant impact on Gross Regional Domestic Product while Zakat, Infaq, Shadaqa and Islamic Human Development Index have a positive but insignificant impact on GRDP. Indirectly, Islamic Human Development Index has not been able to significantly mediate the relationship between labor, ICT-Development Index, and Zakat, Infaq, Shadaqa variables on Gross Regional Domestic Product in Indonesia